Non-EFL Students’ Perception of Grammar and Their Ability in Understanding Basic Grammar - Tira Nur Fitria (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This study describes the students’ perception of grammar and to know their ability in understanding basic grammar. This research is descriptive qualitative. The analysis shows that students like learning English grammar because grammar is a rule or guideline related to English proficiency. But a lot of grammar material must be learned because it is very complicated, complex, and interrelated with other materials. Learning grammar is important for them in mastering writing, speaking, listening, reading, and vocabulary. After learning grammar, the students agree that the lecturer teaches grammar material in a fun way, explains grammar material well accompanied by examples and practice, and then gives assignments as understanding evaluations every meeting. The students can understand grammar lessons in English although the grammar learned in college is more complex than in high school, they do not have any difficulty understanding the material on campus. Grammar helps students to able to communicate orally and written in English better, but they still need to learn more grammar to improve their English skills. However, the result of the tests shows something different from their positive perceptions after learning grammar. The average score is 66.86 from 100 points, the median is 71 from 100 points, and the range from the lowest score of 33 up to 91 points score (correct answer) as the highest score. Further research, of course, still needs to be done to find out the reasons why students' grammar skills show an unsatisfactory average.